The Public Librarian Low-Morale Experience: A Qualitative Study - Davis Kendrick, Kaetrena (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2020)
Recent studies on low morale in academic libraries reveal impacts on workplace health and organizational culture and concerns about leadership training and development. Additionally, established research on library dysfunction and emotional labor in librarianship, along with emerging scholarship on incivility in librarian-patron interactions, highlight a growing area of practice concerns for information professionals. This qualitative study centers public librarians’ experience of low morale. Data validate the development and practice- and health-related outcomes of low morale and illuminate the realities of public library work, organizational culture and behaviours, impact of leadership practices, and the perceptions of the value and role of librarians and the public library in North America.